Band Anti-Crossing Modelling on Tailored Ga1-xInxN yAs1-y Band Gap Energy Based Nitrogen Fraction - Muhammad Izzuddin Abd Samad; Mohammad Syahmi Nordin; Nafarizal Nayan; Afishah Alias; Adrian Boland-Thoms; Anthony John Vickers; Khairul Anuar Mohamad; Marinah Othman (Horizon Research Publishing, 2024)
Indexed by SCOPUS